1976
DOI: 10.3109/00048677609159509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Inpatient Service by Consumer Feedback

Abstract: Over the past few years, the Sound View-Throgs Neck Community Mental Health Center has conducted a number of studies of client satisfaction with our services. The findings suggest that the majority of clients are generally satisfied with the help they receive. However, the level of satisfaction apparently depends on specific aspects or features of the program being evaluated, as well as the particular unit which is providing the services. We have used face-to-face, telephone, and mail survey procedures in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Moreover, in the published studies, where more careful reporting of return rates is likely, response rates are even lower. Of the studies of consumer satisfaction reviewed for this article, 31 indicated return rates; of these 10 report return rates between 21% and 40%, 8 between 41% and 60%, 7 between 61% and 80%, and 6 between 81% and 100% (Ahmed & Koltuv, 1976;Balch, Ireland, Mc-Williams, & Lewis, 1977;Birnbaum & Suits, 1979;Burgoyne, Wolken, Staples, Kline, & Powers, 1977;Ciarlo & Reihman, 1977;Denner & Halprin, 1974a, 1974bEdwards, Yarvis, Mueller, & Langsley, 1978;Fiester & Fort, 1978;Frank, 1974;Getz, Fujita, & Allen, 1975;Gilligan & Wilderman, 1977;Glenn, 1978;Goyne & Ladoux, 1973;Hart & Bassett, 1975;Heineman & Yudin, 1974;Jansen & Aldrich, 1973;Justice & McBee, 1978;Kissel, 1974;Kline, Adrian, & Spevak, 1974;Koltuv et al, 1978;Landsberg, 1975;Love et al, 1979;Mayer & Rosenblatt, 1974;Noll & Block, 1979;Powell et al, 1971;Preston, Schoenfeld, & Adams, 1975;Reinhart & Cazavelan, 1975;Slem & Cotler, 1973;Snelling & Walker, 1978;Strupp, Fox, & Lessler, 1969;Woodward et al, 1978). High rates of return are virtually limited to captive samples in which responses are likely to be highly reactive (typical phone and mail surveys average 41 % and 46% responding, respectively).…”
Section: Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in the published studies, where more careful reporting of return rates is likely, response rates are even lower. Of the studies of consumer satisfaction reviewed for this article, 31 indicated return rates; of these 10 report return rates between 21% and 40%, 8 between 41% and 60%, 7 between 61% and 80%, and 6 between 81% and 100% (Ahmed & Koltuv, 1976;Balch, Ireland, Mc-Williams, & Lewis, 1977;Birnbaum & Suits, 1979;Burgoyne, Wolken, Staples, Kline, & Powers, 1977;Ciarlo & Reihman, 1977;Denner & Halprin, 1974a, 1974bEdwards, Yarvis, Mueller, & Langsley, 1978;Fiester & Fort, 1978;Frank, 1974;Getz, Fujita, & Allen, 1975;Gilligan & Wilderman, 1977;Glenn, 1978;Goyne & Ladoux, 1973;Hart & Bassett, 1975;Heineman & Yudin, 1974;Jansen & Aldrich, 1973;Justice & McBee, 1978;Kissel, 1974;Kline, Adrian, & Spevak, 1974;Koltuv et al, 1978;Landsberg, 1975;Love et al, 1979;Mayer & Rosenblatt, 1974;Noll & Block, 1979;Powell et al, 1971;Preston, Schoenfeld, & Adams, 1975;Reinhart & Cazavelan, 1975;Slem & Cotler, 1973;Snelling & Walker, 1978;Strupp, Fox, & Lessler, 1969;Woodward et al, 1978). High rates of return are virtually limited to captive samples in which responses are likely to be highly reactive (typical phone and mail surveys average 41 % and 46% responding, respectively).…”
Section: Validitymentioning
confidence: 99%
“…3 Among the 26 studies that examine satisfaction in outpatient or in mixed community mental health center populations (which are principally outpatient) and that report summary statistics, 3 find satisfaction in 91%-100% of clients, 10 in 81%-90%, 8 in 71%-80%, 4 in 61%-70%, and 1 in 51%-60% (Balch et al, 1977;Birnbaum & Suits, 1979;Burgoyne et al, 1977;Ciarlo & Reihman, 1977;Denner & Halprin, 1974a, 1974bEdwards etal, 1978;Fiester, 1979;Frank etal., 1977;Gilligan & Wilderman, 1977;Goyne & Ladoux, 1973;Hart & Bassett, 1975;Heineman & Yudin, 1974;Justice & McBee, 1978;Kaufmann, Sorenson, & Raeburn, 1979;Kissel, 1974;Kline et al, 1974;Landsberg, 1973Landsberg, , 1975Love et al, 1979;McCoy, Penick, Powell, & Read, 1975;Noll & Block, 1979;Powell et al, 1971;Reinhart & Cazavelan, 1975;Strupp et al, 1969;Woodward et al, 1978). Among the inpatient studies, 2 show satisfaction in 81%-90% of clients, 2 in 71%-80%, and 2 in 61%-70% (Ahmed & Koltuv, 1976;Eder & Kukulski, 1975;Glenn, 1978;Landsberg, 1973;Mayer & Rosenblatt, 1974;Snelling & Walker, 1978). 4 Among crisis units, 1 study found satisfaction in more than 91% of clients, 2 in 71%-80%, and 1 in 61%-70% (Getz et al, 1975;King, 1977;…”
Section: Level Of Reported Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…810 It is, therefore, not surprising that attempts to measure patient satisfaction, starting in the early 1950s, involved mental health services. 1113…”
Section: Introductionmentioning
confidence: 99%